The European Union’s Activity in Regard to the Conflict in Ukraine Before the 2014 Presidential Election - Rulski, Michał (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
Ukraine is the largest country that is included in European Neighborhood Policy. That is why the European Union should spotlight relations with this eastern partner, especially by foreign policy instruments like association agreement. The focus here is on the EU’s involvement in the Ukrainian crisis in period from Maidan revolution at the end of 2013, which was occasioned by the rejection of the association agreement with the EU by President Viktor Yanukovych, and to the presidential election in 2014. The main issue is to evaluate the EU’s scope to stabilize the political environment in the nearby neighborhood and eliminate threats, which are the results of war between Ukraine and Russia.